Associations among IL-6 Signaling Molecules in Treg Populations in Patients with Relapsing-Remitting Multiple Sclerosis - Magdalena Kierasińska; Maja Machcińska; Marta Maruszewska-Cheruiyot; Ludmiła Szewczak; Anna Karlińska; Rafał Rola; Michael Stear; Katarzyna Donskow-Łysoniewska (Journal of Integrative Neuroscience)
Background: Peripheral immune cells participate in the pathogenesis and progression of central nervous system diseases including relapsing-remitting multiple sclerosis (RRMS), which is an immune-mediated demyelinating disorder. The association between IL-6 and RRMS pathogenesis is clear but there is some uncertainty about the role of IL-6 and IL-6 pathway components in blood and the molecular mechanisms through which T regulatorys (Tregs) contribute to MS pathogenesis. The purpose of this study was to identify markers of IL-6 pathways in serum and regulatory CD8+ and CD4+ T cells in the blood of RRMS patients and to analyze their associations with multiple sclerosis, with each other, and with age. Methods: Peripheral blood was collected from female RRMS patients (16), and healthy controls (18) recruited between December, 2019 and July, 2022. The serum levels of IL-6, TGF-β1, IL-6Rα, IL-6/IL-6Rα complex, and soluble glycoprotein-130 (sgp-130) were measured by ELISA. Flow cytometry was used to quantify the surface expression of IL-6R (CD126), membrane glycoprotein 130 (gp130, CD130), and phospho-STAT3 (pSTAT3) and pSTAT5 in CD4+CD25+FoxP3+, CD8+CD25+FoxP3+, and CD8+CD122+ Tregs. Differences were compared using the Student’s t-test or Welch’s t-test. Pearson product-moment correlations were used to detect correlations. A p-value ≤ 0.05 was considered statistically significant. Results: The CD8+CD122+ Treg subset in RRMS patients exhibited an increased level of surface CD126 and CD130 associated with classical IL-6R signaling without STAT3 phosphorylation. For CD4+CD25+FoxP3+ and CD8+CD25+FoxP3+ Tregs, no changes in classical IL-6R surface markers were observed in RRMS, but there was an increased percentage of pSTAT3 in these cells. Age-related changes in pSTAT5 expression across Treg subsets in healthy controls were absent in RRMS patients. Conclusions: Our findings underscore the complex interplay between IL-6 signaling and Tregs as well as age-related immune regulation. The observed alterations in the expression of receptors and in signaling activity may contribute to the dysregulation of CD8+CD122+ Treg function activated via the classic IL-6 pathway and suggests IL-6 trans-signaling in CD25-positive Tregs. RRMS may interfere with normal immune aging patterns, possibly by promoting a sustained inflammatory state that overrides the senescence of Tregs.